2014
DOI: 10.1042/bst20130279
|View full text |Cite
|
Sign up to set email alerts
|

TGR5 in inflammation and cardiovascular disease

Abstract: TGR5 (Takeda G-protein-coupled receptor 5) [also known as GPBAR1 (G-protein-coupled bile acid receptor 1), M-BAR (membrane-type receptor for bile acids) or GPR131 (G-protein-coupled receptor 131)] is a G-protein-coupled receptor that was discovered as a bile acid receptor. TGR5 has specific roles in several tissues, among which are the regulation of energy expenditure, GLP-1 (glucagon-like peptide 1) secretion and gall bladder filling. An accumulating body of evidence now demonstrates that TGR5 also acts in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…A critical component of adaptive immunity are Th cells that are central in orchestrating immune responses [10]. A number of studies have revealed that plasma bile acid concentrations are, either positively or negatively, correlated to obesity, atherosclerosis and diabetes [11, 12]. Since adaptive immunity and Th cells play a role in these diseases [13, 14], we aimed to identify a potential direct link between bile acids and Th cells.…”
Section: Introductionmentioning
confidence: 99%
“…A critical component of adaptive immunity are Th cells that are central in orchestrating immune responses [10]. A number of studies have revealed that plasma bile acid concentrations are, either positively or negatively, correlated to obesity, atherosclerosis and diabetes [11, 12]. Since adaptive immunity and Th cells play a role in these diseases [13, 14], we aimed to identify a potential direct link between bile acids and Th cells.…”
Section: Introductionmentioning
confidence: 99%
“…49,52,53 TGR-5 activation was shown to be able to induce a significant body weight reduction in mice fed a HF diet, while some studies show TGR5 2/2 mice to have increased body weight and fat content. 53 TGR-5 activation also improves glucose metabolism, insulin sensitivity, and also gastrointestinal motility and appetite, 54 since it was observed that in vitro stimulation of TGR-5 induces GLP-1 secretion by enteroendocrine cells and human intestinal cells. 55À57 Others have shown that the role of TGR5 in metabolic disease is both dependent on gender and diet, especially in terms of insulin sensitivity and fatty liver disease.…”
Section: Dietary Fat Metabolism Bile Acids and Gut Microbiotamentioning
confidence: 97%
“…63 Studies highlighting the multiple roles of the BA-receptors TGR-5 and FXR suggest a complex interplay between metabolic and immune functions, which have important consequences in pathologies characterized by chronic inflammation, such as inflammatory bowel disease (IBD) and the metabolic syndrome and indeed aging. 49,50,53 Diet, especially fermentable fibers or prebiotics, probiotics with bile salt hydrolase activity or bile acid chelating plant polyphenols, will therefore mediate significant physiological effects through the gut microbiota bile acid handling, on both metabolic and inflammatory processes. Morever, as discussed below, the gut microbiota plays a central role in coordinating immunity and metabolism through the intestinal epithelium gene expression pathways.…”
Section: Dietary Fat Metabolism Bile Acids and Gut Microbiotamentioning
confidence: 99%
“…TGR5 is widely expressed including the liver, but absent in hepatocytes. Extensive studies have been done to identify the physiological functions of TGR5 during the last decade (87, 88). However, the role of TGR5 in regulating hepatic lipid metabolism is limited.…”
Section: Bile Acid Receptors In Hepatic Lipid Metabolismmentioning
confidence: 99%